Efficacy of latanoprost in management of chronic angle closure glaucoma - Kumar, S; Malik, A; Singh, M; Sood, S (Nepalese Journal of Ophthalmology, 2010)
Background: Chronic angle closure glaucoma is often managed surgically. Aim: To study the effect of Latanoprost 0.005% on intraocular pressure in subjects diagnosed as having chronic angle closure glaucoma. Materials and methods: Forty patients participated in the study. Baseline examination included visual acuity, refraction, slit-lamp examination, intraocular pressure, anterior and posterior segment examination, gonioscopy and perimetry. Patients were treated with Latanoprost 0.005% once daily at bedtime. IOP was recorded at baseline, 2weeks, 4 weeks, 8 weeks and 12 weeks after starting the treatment. Results: The mean age of the study sample was 56.45 years (40-70 years). There were 18 males and 22 females in the study. Mean IOP at baseline was 24.55±3.63. Mean IOP decreased to 17.27±3.19 at 2 weeks, 15.27±3.07 at 4 weeks, 14.60±3.06 at 8 weeks and 14.47±2.66 at 12 weeks. There was a statistically significant reduction in mean IOP (41.03%) at 12 weeks as compared to those of the baseline IOP (p=0.000). There was no significant difference in IOP reduction in eyes with different degrees of angle closure by peripheral anterior synechiae. Conclusion: Latanoprost, a prostaglandin analogue, is effective in reducing IOP in chronic angle closure glaucoma patients and its efficacy is not affected by the degree of angle closure by peripheral anterior synechiae. Key words: latanoprost; chronic angle closure glaucoma; intraocular pressure; peripheral anterior synechiae DOI: 10.3126/nepjoph.v1i1.3671 Nep J Oph 2009;1(1):32-36